2017
DOI: 10.15420/cfr.2017:3:2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Atrophy and Heart Failure In Cancer

Abstract: Functional changes in the heart in patients with cancer can be a result of both the disease itself and various cancer therapies, and limiting cardiac damage has become an increasingly important issue as survival rates in patients with cancer have improved. Processes involved in cancer-induced cardiac atrophy may include cardiomyocyte atrophy and apoptosis, decreased protein synthesis, increased autophagy and proteolysis via the ubiquitin-proteosome system. Further to direct effects of malignancy on the heart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Although most focus is on CTAC, there are also direct effects of cancer on the CV system. Eighty percent of all cancer patients show significant loss in muscle strength and weight, including muscle cells of the heart [14]. More than 50 years ago, Burch et al noticed that patients who died of cancer had smaller hearts, reduced total mass, and smaller left ventricular (LV) wall thickness [15].…”
Section: Cancer An Independent Risk Factor For Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most focus is on CTAC, there are also direct effects of cancer on the CV system. Eighty percent of all cancer patients show significant loss in muscle strength and weight, including muscle cells of the heart [14]. More than 50 years ago, Burch et al noticed that patients who died of cancer had smaller hearts, reduced total mass, and smaller left ventricular (LV) wall thickness [15].…”
Section: Cancer An Independent Risk Factor For Cvdmentioning
confidence: 99%
“…More than 50 years ago, Burch et al noticed that patients who died of cancer had smaller hearts, reduced total mass, and smaller left ventricular (LV) wall thickness [15]. Cancer cells alter metabolic pathways by inducing the catabolic state in muscle cells, which leads to cardiac cachexia [14]. More recently, Pavo et al reported that circulating cardiac biomarkers NT-proBNP and hsTnT increased with advancing tumor stage even before starting antineoplastic treatments [16].…”
Section: Cancer An Independent Risk Factor For Cvdmentioning
confidence: 99%
“…DOX induces cardiomyocyte death, one of mechanisms responsible for DOX-induced cardiac atrophy and functional impairment. 27 Given our findings that PDE1C and A 2 R regulate cardiomyocyte death, we investigated whether they could also modulate DOX-induced cardiotoxicity. Similar to Ang II induced myocyte death, the PDE1 inhibitor IC86340 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction in cancer has been reported to occur in the form of mitochondrial uncoupling, reduced ATP production, and NFkB-MAPK-dependent mitochondrial disorder [11,12]. In addition, it has been reported that cardiomyocyte atrophy, apoptosis induction, and decrease in protein synthesis by enhanced autophagy and activation of the ubiquitin-proteasome system lead to cancer-derived myocardial impairment [13].…”
Section: Introductionmentioning
confidence: 99%